The Sport Expert's Attention Superiority on Skill-related Scene Dynamic by the Activation of left Medial Frontal Gyrus: An ERP and LORETA Study. (21st May 2018) - He, Mengyang; Qi, Changzhu; Lu, Yang; Song, Amanda; Hayat, Saba Z.; Xu, Xia
Graphical abstract: Highlights: ERP results showed that the experts had an increased attentional processing associated with skill-related scene information. The LORETA showed that this attentional function was dynamically driven by left MFC and probably due to self-reference. These findings reveal the mechanism why the experts have so many perceptual priorities. Our study provides theoretical and practical support for subsequent expert vs. novice studies in sports field. Abstract: Extensive studies have shown that a sports expert is superior to a sports novice in visually perceptual-cognitive processes of sports scene information, however the attentional and neural basis of it has not been thoroughly explored. The present study examined whether a sport expert has the attentional superiority on scene information relevant to his/her sport skill, and explored what factor drives this superiority. To address this problem, EEGs were recorded as participants passively viewed sport scenes (tennis vs. non-tennis) and negative emotional faces in the context of a visual attention task, where the pictures of sport scenes or of negative emotional faces randomly followed the pictures with overlapping sport scenes and negative emotional faces. ERP results showed that for experts, the evoked potential of attentional competition elicited by the overlap of tennis scene was significantly larger than that evoked by the overlap of non-tennis scene, while this effect was absent for novices. The LORETA showed that the experts' left medial frontal gyrus (MFG) cortex was significantly more active as compared to the right MFG when processing the overlap of tennis scene, but the lateralization effect was not significant in novices. Those results indicate that experts have attentional superiority on skill-related scene information, despite intruding the scene through negative emotional faces that are prone to cause negativity bias toward their visual field as a strong distractor. This superiority is actuated by the activation of left MFG cortex and probably due to self-reference.